Utilization of Household Waste Media in Project-Based Learning to Improve Students' Eco-literacy and Creativity (Journal of Primary Education, 2022)
This research is motivated by household waste that has not been managed properly so that a learning approach is needed that is built from real student activities. This study aims to analyze whether there is an improvement in students' eco-literacy and creativity. The research method used a quasi-experimental design. The experimental group was taught using the project-based learning model that used household waste in the form of used goods media and the control group was taught using the group investigation model that used household waste media. The instruments used multiple-choice test questions on eco-literacy and test questions on students' creativity on the theme of heat and its displacement. Data collection consists of the performance test. The data analysis technique used the research prerequisite tests. Meanwihle, hypothesis testing using the average difference test and the N-gain test. The average eco-literacy ability exceeds the minimum criteria, the proportion of classical completeness is more than 75%, and the average class with the utilization of household waste based on project-based learning is better than that of the class before this lesson. It can be concluded that there is an improvement in students' eco-literacy and creativity in teaching with household waste media in project-based learning.